1921
DOI: 10.5962/bhl.title.20172
|View full text |Cite
|
Sign up to set email alerts
|

Breeding crop plants

Abstract: Classification and inheritance in barley Species crosses 99 Simple Mendelian characters Winter versus spring habit 103 Density of the spike 103 The barley awn in relation to yield Some rye studies Wheat-rye hybrids Buckwheat Breeding buckwheat Rice Inheritance of characters CHAPTER VIII METHODS OF BREEDING SMALL GRAINS Method of keeping continuous records Ill New introductions 113 Select'on 114 Summary of methods of selection 115 Crossing 116 Technic of harvesting, thrashing, etc CHAPTER IX SOME RESULTS OF SEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1924
1924
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
(80 reference statements)
0
15
0
Order By: Relevance
“…Smooth-awned barley, in contrast, does not have such teeth. Awn texture is controlled by a major gene, R/r (Hayes and Garber, 1921;Wexelsen, 1934). The R allele is completely dominant to r. With regard to awn texture, both Awnless and Full-awned Atlas are rough-awned, whereas the other parents, Bonanza, Galt and Minnesota 5 are smooth-awned.…”
Section: Single Cross Populatiommentioning
confidence: 98%
“…Smooth-awned barley, in contrast, does not have such teeth. Awn texture is controlled by a major gene, R/r (Hayes and Garber, 1921;Wexelsen, 1934). The R allele is completely dominant to r. With regard to awn texture, both Awnless and Full-awned Atlas are rough-awned, whereas the other parents, Bonanza, Galt and Minnesota 5 are smooth-awned.…”
Section: Single Cross Populatiommentioning
confidence: 98%
“…Hayes and Immer (1942) defined combining ability as the relative ability of a biotype to transmit desirable performance to its crosses. Inbreds must yield enough to make seed corn production profitable (Hayes and Garber, 1921). Richey (1924) and Richey and Mayer (1925) found that certain inbreds gave higher yielding crosses.…”
Section: Corn Hybridsmentioning
confidence: 99%
“…Hayes and Garber (7) state that Pridham observed a natural cross between Avena sterilis and A. nuda in rgr6. These authors consider that numerous statements by breeders as to self-fertilization show that natural crossing occurs much less frequently in oats than in wheat.…”
Section: Review Of Literaturementioning
confidence: 99%
“…These statements from different investigators indicate that their opinions vary as to the amount of natural crossing which may occur in oats. Jamieson (u) who believed that natural crossing in oats occurs very commonly, is contrasted with McAlpine (15), Norton (14), Hays (8), Hunt (9), Pope (17), Love and Craig (13), Fraser (6), and Hayes and Garber (7), who believe that natural crossing seldom occurs.…”
Section: Review Of Literaturementioning
confidence: 99%